Study on Building Defect by Using Non-Destructive Test at Masjid Jamek Panchor, Muar, Johor - Muhamad, Ahmad Nazmi; Abdul Rahman, Mohd Fahmi; Abdul Rahman, Mohammad Ashraf (Progress in Engineering Application and Technology, 2022)
An existing concrete building will be deteriorating with time due to various factors and bring impact on concrete durability and structural safety. Therefore, assessing the current concrete strength of the existing building is necessary for ensuring safety. Hence, the objectives of this study are to identify the types of building defects that occur at Masjid Jamek Panchor, Muar, Johor to measure the defect by using the Non-Destructive Test method and to recommend the solution to conserve the building. Therefore, visual inspection was conducted at the beginning to achieve the first objective. Additionally, the Rebound Hammer Test and Ultrasonic Pulse Velocity Test were conducted on eight selected columns. The collected data correlated with concrete strength and concrete quality created by previous researchers to achieve the second objective. Lastly, three recommendations to conserve the building were proposed. Based on the data collected from both tests, it was found that the highest concrete strength of the column is column 2 with 45 N/mm2 (based on Rebound Hammer data) and column 8 with V=3733 (based on Ultrasonic Pulse Velocity data). In conclusion, most of the concrete strength of elements is more than 45 N/mm2, and concrete quality is considered as good although defects appeared.